Analyzing the barriers to purchase intentions of energy efficient appliances from consumer perspective. Issue 5 (19th February 2019) - Joshi, Gauri Yogesh; Sheorey, Pratima Amol; Gandhi, Aradhana Vikas
Abstract : Purpose: The purpose of this paper is to identify the barriers to consumers' intention to purchase energy efficient appliances. It uses multiple regression analysis to predict the factors that deter consumers' purchase intention. Design/methodology/approach: Five barriers to consumers' intention to purchase energy efficient appliances were identified through an exhaustive literature survey. Data were gathered from 300 respondents from Pune city from the state of Maharashtra in India through a survey. The items were measured on a five-point Likert scale. Validity and reliability of the scale were established. Multiple regression analysis was conducted to predict consumers' intention to purchase energy efficient appliances based on factors identified. Findings: Findings revealed that some degree of uncertainty was associated with energy efficient appliance purchase. In addition to possessing lower degrees of awareness on energy efficient appliances, consumers tend to disbelieve claims made on labels of energy efficient appliances. Consumers also feel inconvenience in identifying these appliances, spending time to know about them and paying the price to purchase them. Hence, the factors – scepticism towards label claims and perceived personal inconvenience – were found to have negative impact on consumers' purchase intention. Societal norm was found to have a positive impact on consumers' purchase intention. Interestingly, price sensitivity and perceived product risk (which were expected to have a negative relationship with consumers' purchase intention) displayed a positive relationship. Research limitations/implications: The model proposed here is based on the researcher's identification of the barriers. There might have been unidentified barriers that were not considered. The research does not account for manufacturing or policy-based issues that might also pose as barriers. The study encourages marketers to re-examine marketing and communication policies associated with the sale of energy efficient appliances. Originality/value: The paper provides insights into the external barriers faced by consumers while purchasing an energy efficient appliance. This research enables managers to understand consumer's preference for conventional products over energy efficient ones. It attempts to check the presence of barriers to energy efficient appliances, identified from literature in a tier 1 city of India. Tier 1 city is the city with population greater than 1, 00, 000 as per 2001 census of India.